Never cry wolf - Mowat, Farley (Back Bay Books / Little, Brown and Company, 2001)
A Canadian biologist's assignment to study arctic wolves in 1948 turns up many unusual facts about their pattern of living, eventually softening the species' savage reputation worldwide.